Elevating game experiences with Unreal Engine 5 : bring your game ideas to life using the new Unreal Engine 5 and C++ /: bring your game ideas to life using the new Unreal Engine 5 and C++. (2022) - Marques, Gonçalo; Sherry, Devin; Pereira, David; Fozi, Hammad
No abstract available